Non-invasive prenatal testing as a routine procedure of prenatal care: Perspectives and challenges regarding reproductive autonomy - Rubeis, Giovanni; Orzechowski, Marcin; Steger, Florian (Ethik in der Medizin, 2019)
In March 2019, the German Gemeinsamer Bundesausschuss (G‑BA; Federal Joint Committee) presented the result of the method assessment process on non-invasive prenatal testing (NIPT). The aim of this method assessment process was to decide whether NIPT should become a publicly funded procedure of routine prenatal care. The G‑BA decided in favor of NIPT, making the implementation of NIPT very likely, provided that other healthcare and political institutions also agree.